Social Movements: Experiences in the Philippines (Aya Fabros, Joel Rocamora, and Djorina Velasco, eds.) - Chng, Nai Rui (Kasarinlan: Philippine Journal of Third World Studies; Vol 22 No 2 (2007): Culture and Identity, 2008)
Review of Social Movements: Experiences in the Philippines.
Keywords: Social Movements,Philippines